A comparison of pre-operative and post-operative use of 10% lignocaine aerosol for post-tonsillectomy pain relief in paediatric patients - Dalwadi, Bhavesh K.; Dalwadi, Jigna B. (International Journal of Research in Medical Sciences, 2017)
Background: Tonsillectomy surgery is most commonly carried out in paediatric age group. Pain relief after tonsillectomy in children remains a dilemma for anaesthesia. Rapid recovery from anaesthesia and return of protective relflexes are desirable earliest. There are conventional methods for pain relief post-tonsillectomy but use of local anaesthetic agents provide pain relief without any adverse effect. Hence we carried out our study in 4-12 years of age group and compare efficacy of pre-operative and post-operative 10% lignocaine aerosol for post-tonsillectomy pain relief. Methods: After institutional approval and informed consent 75 ASA I AND II children in 4-12 years of age group undergoing tonsillectomy were taken. In group A children did not receive any local anaesthetic whereas in group B children received 10% lignocaine aerosol pre-operative 3 minutes prior tonsillectomy and group C children received post-tonsillectomy aerosol in tonsillar fossa raw area. Anaesthetic management was standardized. Post-operative pain assessment done via behavioural scale. Results: The mean age, weight and duration of surgeries were not significantly different when compared in all three groups. In both study group B and C duration of analgesia is comparable in postoperative period. In both group no analgesia required upto 3 hours after surgery. In group C recovery was delayed compared to group B. Conclusions: The use of 10% lignocaine aerosol is easy, safe and effective method for post-tonsillectomy pain relief in paediatrics.